Validity of Science Teaching Module Integrated with “Engklek” Games to Improve Critical Thinking Skills - Mukaromah, Siti Zumrotun; Septiana Sari, Dwi; Nugraheni, Diah (Pendidikan Kimia Unimus, 2024)
The independent curriculum teaching module is a systematically arranged learning equipment, containing the components of the teaching module and the dimensions of the Pancasila Student Profile. The purpose of this study was to test the feasibility of the science teaching module of the critical reasoning dimension with the project-based learning (PjBL) model through differentiated learning integrated with the Engklek game. This research uses a quantitative descriptive approach and the module tested for feasibility has been prepared using the 4D (four D) research and development model. The feasibility test consists of validity testing by learning expert lecturers, media expert lecturers, practicality by science educators, and readability by class VIII students at SMP Negeri 3 Ungaran. The results of the study showed that the average validity of the teaching module was 91%, which means it is in a very valid category and the reliability of the validation instrument was 95% based on Percentage of Agreement, which means it is in a very good category. Thus, the science teaching module of Critical Reasoning Dimension through Differentiated Learning Integrated with Engklek Game which focuses on the material of Work, Energy, and Simple Machinery is feasible to be implemented.